HUBUNGAN KARAKTERISTIK PASIEN PNEUMONIA DENGAN DERAJAT KEPARAHAN PNEUMONIA PADA ANAK BALITA DI RS SITI KHODIJAH MUHAMMADIYAH SEPANJANG TAHUN 2019-2020 - Lia Lisa Arista; Yudith Annisa A. R.; Gina Noor Djalilah; Edim Hartati (Universitas Muhammadiyah Surabaya, 2023)
Background/aim: Globally, pneumonia is the leading cause of morbidity and mortality in children younger than five years old. Several studies reveal that age, gender, vaccination status, and nutritional status are associated with severity and mortality in children with pneumonia, so further research is needed. This study aims to determine the characteristic of pneumonia such as age, gender, vaccination status, and nutritional status with the severity of pneumonia among children below five years old at Siti Khodijah Muhammadiyah Hospital. Material and Methods : A retrospective cross-sectional study using medical record data among children below five years old who were treated with a final diagnosis of pneumonia/bronchopneumonia at Siti Khodijah Muhammadiyah Hospital during January 2019 to December 2020 were obtained. The data were analyzed by Chi-square test and multivariate analyzed was performed including variables that were significant at p<0,05 in bivariate analyzed. Result : The characteristic related to the severity of pneumonia among children below five years old are age (P= 0.042) and nutritional status (P = 0.015). Children under five with underweight are 4,700 times more likely to have severe pneumonia than those with overweight. Children aged 1-12 months are at risk for severe pneumonia 3.239 times greater than those aged 36-60 months. This study concluded that younger age and underweight wereÂ risk factorsÂ forÂ severe pneumonia. Originality/ Value/ Implication : Thepaper provides a new interpretation of existing sources on the characteristics of pneumoniapatients and offers new insights into the topic area by emphasizing its relationship with severity of pneumonia.Keywords: pneumonia, characteristic features, severity, pediatric